2012
DOI: 10.1002/adfm.201102758
|View full text |Cite
|
Sign up to set email alerts
|

Lone‐Pair‐Induced Covalency as the Cause of Temperature‐ and Field‐Induced Instabilities in Bismuth Sodium Titanate

Abstract: (JARA). This is one of the first Nature-branded conferences in the physical sciences, and the emphasis is on presenting groundbreaking scientific research and to foster stimulating discussions. Aachen is the ideal place for such a conference, with its central location in Europe, its long history, and most of all its strong local research culture. We hope you have a splendid time in Aachen: enjoy the presentations, have stimulating discussions, and find the conference beneficial to your future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
215
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 454 publications
(232 citation statements)
references
References 59 publications
15
215
0
Order By: Relevance
“…This study also confirms generally accepted knowledge that the 6s 2 lone pair electronic structure of Bi 3+ ions plays a crucial role in anion migration of many Bibased oxide ion conductors 22,23 and extends the class of close packed structures from fluorites such as -Bi 2 O 3 to A-site Bi-based perovskites. 10 By adding a small excess of Bi 2 O 3 to the starting composition, i.e.…”
Section: Introductory Paragraphsupporting
confidence: 74%
See 1 more Smart Citation
“…This study also confirms generally accepted knowledge that the 6s 2 lone pair electronic structure of Bi 3+ ions plays a crucial role in anion migration of many Bibased oxide ion conductors 22,23 and extends the class of close packed structures from fluorites such as -Bi 2 O 3 to A-site Bi-based perovskites. 10 By adding a small excess of Bi 2 O 3 to the starting composition, i.e.…”
Section: Introductory Paragraphsupporting
confidence: 74%
“…NBT has an ABO 3 perovskite-type structure but the crystal chemistry is complex with differences in the average and local structure being reported depending on the characterisation techniques used and whether the samples are ceramics or single crystals [12][13][14][15][16][17][18][19][20][21][22] . On an average scale, based on neutron powder diffraction studies 12 , NBT is reported to exhibit a sequence of phase transitions (on cooling) from a high temperature cubic (space group Pm m), to tetragonal (space group, Pb4m) and then to a room temperature (RT) rhombohedral (space group R3c) structure.…”
Section: Crystal Structure and Ferroelectric Domain Structuresmentioning
confidence: 99%
“…At T d , the inter-atomic spring constant responsible for the total energy of the mode was lowered abruptly, accompanied by a rapid change in symmetry of the whole crystal system. 42) This is a hallmark of the breaking of a covalent bond.…”
Section: )41)mentioning
confidence: 99%
“…The defect chemistry of NBT is rather different from other well-known titanates such as (Ba,Sr,Ca)TiO 3 in that the electrical conductivity is dominated by oxide-ion conduction in NBT and NB 0.49 T rather than electronic conduction. We have attributed the differences in behaviour and the high oxide-ion conductivity in these compositions to high oxygen ion mobility associated with highly polarised Bi 3+ cations and weak Bi-O bonds 31 as well as oxygen vacancies generated through loss of a small amount of Bi 2 O 3 during ceramic processing according to the Kroger-Vink equation, and clarify the origin(s) of its effect on electrical properties. We also highlight the importance of drying Na 2 CO 3 prior to ceramic processing as small changes in the nominal starting stoichiometry of this hygroscopic reagent influences the electrical properties of NBT ceramics.…”
Section: Introductionmentioning
confidence: 99%